2016
DOI: 10.1186/s40623-016-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating P- and S-wave velocity structure beneath the Marmara region (Turkey) and the surrounding area from local earthquake tomography

Abstract: We investigated the crustal structure beneath the Marmara region and the surrounding area in the western part of the North Anatolian fault zone. These areas have high seismicity and are of critical significance to earthquake hazards. The study was based on travel-time tomography using local moderate and micro-earthquakes occurring in the study area recorded by the Multi-Disciplinary Earthquake Research in High Risk Regions of Turkey project and Kandilli Observatory and Earthquake Research Institute. We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The crustal structure in our study region has been characterised using a wide variety of geophysical techniques including seismic refraction (Karahan et al, 2001;Horasan et al, 2002;Bekler & Gürbüz, 2008), ambient noise (Taylor et al, 2016(Taylor et al, , 2019a, receiver functions (Vanacore et al, 2013;Jenkins et al, 2020), local earthquake tomography (Bariş et al, 2005;Koulakov et al, 2010;Beyhan & Alkan, 2015;Polat et al, 2016;Yolsal-Çevikbilen et al, 2012), magnetotellurics (Tank et al, 2005), and regional full waveform tomography (Fichtner et al, 2013;Çubuk-Sabuncu et al, 2017). Similarly, the upper mantle has been studied using receiver functions (Kind et al, 2015;Taylor et al, 2019b), seismic anisotropy (Biryol et al, 2010;Paul et al, 2014;Lemnifi et al, 2017;Legendre et al, 2021) and body and surface wave tomography (Berk Biryol et al, 2011;Bakırcı et al, 2012;Salaün et al, 2012;Fichtner et al, 2013;Govers & Fichtner, 2016;Papaleo et al, 2017Papaleo et al, , 2018.…”
Section: Tectonics and Previous Geophysical Surveysmentioning
confidence: 99%
“…The crustal structure in our study region has been characterised using a wide variety of geophysical techniques including seismic refraction (Karahan et al, 2001;Horasan et al, 2002;Bekler & Gürbüz, 2008), ambient noise (Taylor et al, 2016(Taylor et al, , 2019a, receiver functions (Vanacore et al, 2013;Jenkins et al, 2020), local earthquake tomography (Bariş et al, 2005;Koulakov et al, 2010;Beyhan & Alkan, 2015;Polat et al, 2016;Yolsal-Çevikbilen et al, 2012), magnetotellurics (Tank et al, 2005), and regional full waveform tomography (Fichtner et al, 2013;Çubuk-Sabuncu et al, 2017). Similarly, the upper mantle has been studied using receiver functions (Kind et al, 2015;Taylor et al, 2019b), seismic anisotropy (Biryol et al, 2010;Paul et al, 2014;Lemnifi et al, 2017;Legendre et al, 2021) and body and surface wave tomography (Berk Biryol et al, 2011;Bakırcı et al, 2012;Salaün et al, 2012;Fichtner et al, 2013;Govers & Fichtner, 2016;Papaleo et al, 2017Papaleo et al, , 2018.…”
Section: Tectonics and Previous Geophysical Surveysmentioning
confidence: 99%
“…The NAFZ has been subject to several seismic experiments, the data from which have been analysed using a variety of methods. In the early 2000s, relationships between seismicity and crustal velocity structure beneath the NAFZ were investigated by local earthquake tomography (Nakamura et al 2002;Yolsal-Ç evikbilen et al 2012;Polat et al 2016;Ç ubuk-Sabuncu et al 2017) and active-source seismic tomography (e.g. Karabulut et al 2003;Bayrakci et al 2013) in the Marmara Sea region.…”
Section: P R E V I O U S S E I S M O L O G I C a L W O R Kmentioning
confidence: 99%
“…In contrast, autocorrelation of ambient seismic noise suggests a substantial Moho offset related to the northern branch of the NAFZ in the same region, while no such offset is observed on the southern branch (Taylor et al 2016). Polat et al (2016) carried out local P-and S-wave tomography to image 3-D seismic velocity variations across different branches of the NAFZ in the Marmara Sea region. They found that high-velocity anomalies appear to be coincident with the rupturing segments of the NAFZ where most of the observed high seismicity is concentrated.…”
Section: P R E V I O U S S E I S M O L O G I C a L W O R Kmentioning
confidence: 99%
“…Over the last decade, many regional-and local-scale tomography studies were performed for different parts of Turkey. Seismic velocity models of the lithosphere were obtained for the areas of central Anatolia [31,32], western Turkey [33], eastern Turkey [34,35], the North Anatolian fault [36][37][38], the Marmara Basin [39,40], and the Erzincan Basin [41].…”
Section: Introductionmentioning
confidence: 99%